USE OF INNOVATIVE TECHNOLOGIES IN TEACHING THE SUBJECT "THEORETICAL MECHANICS" (Archive of Conferences, 2022)
The article shows the role of innovative pedagogical technologies in teaching the subject "Theoretical Mechanics". He gives an example of the use of some innovative methods.